Pengembangan metode permainan kimia estafet pada sub materi tata nama senyawa alkana di SMA Negeri 9 pontianak - Susana Tia; Raudhatul Fadhilah; Dedeh Kurniasih (Universitas Muhammadiyah Pontianak, 2020)
Based on the results of teacher interviews low student learning outcomes on sub-material the name of an alkylatine compound because students have not mastered the rules of naming compounds alkyana. The method used in learning is the lecture method. The purpose of this research is to develop a valid learning method, the very and effective conducted in SMA Negeri 9 Pontianak kelasd XI Mia 1 and Mia 3. The type of research used is Research and Dovelopment (R&D). The research and development of chemical relay game method is done through 7 stages of research: data collection, planning, initial product development, initial field trial, initial product revision, main field trials, revision of operational product in class XI students MIA 1 which amounted to 35 people and involving 1 teacher. Results of the analysis showed that the game validation of the chemical relay of the material and media aspects of each of 0.94 and 0.87 with very valid criteria. The percentage of the student response poll and the initial field test teacher and main field test respectively amounted to 97.5% and 92.93% are included in highly-pratist criteria. The results of N-Gain analysis on the initial field trials and main field trials were obtained at a value of 0.83 and 0.90 of high criteria respectively. Thus the methods of the chemical relay game developed worthy of use as a method of learning on sub-material of the name of the Alkyana compound in the XI high school class.